2017
DOI: 10.1002/term.2401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cell cycle phases on the induction of dental pulp stem cells toward dopaminergic‐like cells

Abstract: Parkinson's disease (PD) is characterized by tremors and cognitive issues, and is due to the death of dopaminergic (DA-ergic) neurons in brain circuits that are responsible for producing neurotransmitter dopamine (DA). Currently, cell replacement therapies are underway to improve upon existing therapeutic approaches such as drug treatments and electrical stimulation. Among the widely available sources, dental pulp stem cells (DPSCs) from deciduous teeth have gained popularity because of their neural crest orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…1). This further confirms the applicability of DPSCs as a suitable cell source for CRT especially in PD cases (49). Although the fact that apoptosis can also invariably take place in this situation is undeniable, our study did not look into this aspect as one of vital parameter.…”
Section: Discussionsupporting
confidence: 69%
“…1). This further confirms the applicability of DPSCs as a suitable cell source for CRT especially in PD cases (49). Although the fact that apoptosis can also invariably take place in this situation is undeniable, our study did not look into this aspect as one of vital parameter.…”
Section: Discussionsupporting
confidence: 69%
“…At 24 h time point post‐incubation with various LPS concentration, the release of cytokines were assessed via ELISA as described earlier (Gnanasegaran et al, ). From the collected supernatant, presence of IL‐6, IL‐8, IL‐1α and TNF α was detected using Tecan micro plate reader (Infinite 200 PRO Tecan, Life sciences, Switzerland) with test wavelength adjusted at 450 nm and reference wavelength at 650 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of Chang et al reported that DPSCs could be directly differentiated into motor neurons by growth factors and small molecules, for example, BDNF and all-trans retinoic acid [ 71 ]. Gnanasegaran et al demonstrated that DPSCs could be induced to differentiate into dopaminergic-like cells by multistage inductive protocols [ 72 ]. The study of Singh et al showed that DPSCs are induced by a two-step method to generate functional dopaminergic neurons: FGF2 first with an addition of BDNF on 9th day.…”
Section: Dental Pulp Stem Cells (Dpscs)mentioning
confidence: 99%